2019
DOI: 10.1021/acs.biochem.9b00292
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate 5-Hydroxylase: Intermediates in Aromatic Hydroxylation by a Rieske Monooxygenase

Abstract: Rieske oxygenases (ROs) catalyze a large range of oxidative chemistry. We have shown that cis-dihydrodiol-forming Rieske dioxygenases first react with their aromatic substrates via an active site nonheme Fe­(III)-superoxide; electron transfer from the Rieske cluster then completes the product-forming reaction. Alternatively, two-electron-reduced Fe­(III)–peroxo or hydroxo–Fe­(V)–oxo activated oxygen intermediates are possible and may be utilized by other ROs to expand the catalytic range. Here, the reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 90 publications
1
62
0
Order By: Relevance
“…2 E ). As it is known that substrate binding can be required for the activation of the catalytic mononuclear Fe center to initiate catalysis ( 42 , 43 ), the substrate (carnitine) was added to the reaction and the EPR spectrum was monitored ( Fig. 2 C , cyan trace).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 E ). As it is known that substrate binding can be required for the activation of the catalytic mononuclear Fe center to initiate catalysis ( 42 , 43 ), the substrate (carnitine) was added to the reaction and the EPR spectrum was monitored ( Fig. 2 C , cyan trace).…”
Section: Resultsmentioning
confidence: 99%
“…None of the E205 mutants that we generated in this study were active ( Figure 2D), with no major perturbations to the overall secondary structure as observed by circular dichroism (Figure 2E). As it is known that substrate-binding can be required for the activation of the catalytic mononuclear Fe centre to initiate catalysis (42)(43), the substrate (carnitine) was added to the reaction and the EPR spectrum was monitored ( Figure 2C, cyan trace). The spectrum shows no EPR signals at low magnetic fields, ruling out the presence of high-spin (S = 5/2 or 3/2) ferric species in the sample.…”
Section: Structural Basis Of Long-distance Electron Transfer and Epr mentioning
confidence: 99%
“…To accomplish selective modification of inert C-H bonds, these enzyme classes employ molecular oxygen to generate high-valent iron intermediates, which activate a substrate for hydroxylation through hydrogen atom abstraction [7][8][9][10][11] . Examples include the Fe(IV)-oxo and Fe (III)-hydroperoxo intermediates employed by heme-containing systems 12,13 and the Fe(III)-superoxo 14 , Fe(IV)-oxo, or proposed Fe(V)-oxo species used by non-heme systems 7 . In the Rieske oxygenase class, work to date has been conducted on a small sample of enzymes, specifically those that perform dioxygenation of aromatic rings.…”
mentioning
confidence: 99%
“…Our data are in agreement with those previously reported for NDO from Pseudomonas sp. [7,15]. Proteins containing the [2Fe-2S] clusters exhibit this characteristic EPR signature, formed of one g -value just above g = 2 (range: 2.01–2.05) and two g -values below g = 2 typically between 1.85 and 1.95.…”
Section: Resultsmentioning
confidence: 99%
“…Recently [15] it has been reported that the Fe(II) mononuclear iron and the one-electron reduced Rieske cluster are able to catalyse the dihydroxylation of naphthalene in the absence of NDR and NDF in a single turnover reaction [7]. Naphthalene and molecular oxygen react with NDO to form an amount of product that is stoichiometric with the concentration of the mononuclear Fe(II) sites.…”
Section: Introductionmentioning
confidence: 99%